1993
DOI: 10.1073/pnas.90.16.7436
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory subunits of cAMP-dependent protein kinases are degraded after conjugation to ubiquitin: a molecular mechanism underlying long-term synaptic plasticity.

Abstract: In Aplysia, behavioral sensitization of defensive reflexes and the underlying presynaptic facilitation of sensory-to-motor neuron synapses lasts for several minutes (short term) or days to weeks (long term). Short-term sensitization has been explained by modulation ofion-channel function through cAMP-dependent protein phosphorylation. Long-term facilitation requires additional molecular changes including protein synthesis. A key event is the persistent activation of the cAMP-dependent protein kinase at baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
137
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(143 citation statements)
references
References 45 publications
6
137
0
Order By: Relevance
“…On the other hand, activation of the proteosomal pathway and proteases might remove inhibitory constraints at the synapse to create and maintain a permissive environment for synaptic growth. The involvement of Uch and ubiquitin-mediated protein-turnover pathways in synaptic plasticity has previously been observed in Aplysia and in mice (24)(25)(26)(27)(28). Because ubiquitination can act as a posttranslational modification in addition to a signal for degradation, the ubiquitination pathway can, in principle, modulate stability, function, or membrane distribution of proteins at the activated synapse.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, activation of the proteosomal pathway and proteases might remove inhibitory constraints at the synapse to create and maintain a permissive environment for synaptic growth. The involvement of Uch and ubiquitin-mediated protein-turnover pathways in synaptic plasticity has previously been observed in Aplysia and in mice (24)(25)(26)(27)(28). Because ubiquitination can act as a posttranslational modification in addition to a signal for degradation, the ubiquitination pathway can, in principle, modulate stability, function, or membrane distribution of proteins at the activated synapse.…”
Section: Discussionmentioning
confidence: 95%
“…The first discovery of ubiquitin-proteasome-mediated degradation of a substrate relevant to synaptic plasticity in the nervous system was that of R subunits of PKA (Hegde et al 1993). Since then several substrates of the UPP in the nervous system have been identified (Hegde 2010).…”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 99%
“…What is the mechanism of R subunit degradation? Hegde et al (1993) found through a series of biochemical experiments that R subunits were substrates for ubiquitination and proteasome-mediated degradation. Moreover, a UCH ([Ap-uch] Aplysia ubiquitin C-terminal hydrolase ) that interacts with the proteasome was found to be induced by serotonin, the neurotransmitter that induces LTF.…”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 99%
“…Degradation of the R subunits can then result in sustained PKA activity that outlasts the cAMP signal (44). RNAi against PKAR1A has recently been found to increase basal and stimulated PKA activity in HEK293 cells (45).…”
Section: Reduction In Pka C1 Subunit Expression Correlates With Reducedmentioning
confidence: 99%